Ultralow-Dose Abdominal Computed Tomography. Issue 4 (July 2015) - Khawaja, Ranish Deedar Ali; Singh, Sarabjeet; Blake, Michael; Harisinghani, Mukesh; Choy, Gary; Karosmanoglu, Ali; Padole, Atul; Pourjabbar, Saravenaz; Do, Synho; Kalra, Mannudeep K.
<x xml:space="preserve">Abstract</x> Purpose To assess lesion detection and image quality of ultralow-dose (ULD) abdominal computed tomography (CT) reconstructed with filtered back projection (FBP) and 2 iterative reconstruction techniques: hybrid-based iDose, and image-based SafeCT. Materials and Methods In this institutional review board–approved ongoing prospective clinical study, 41 adult patients provided written informed consent for an additional ULD abdominal CT examination immediately after standard dose (SD) CT exam on a 256-slice multidetector computed tomography (iCT, Philips-Healthcare). The SD examination (size-specific dose estimate, 10 ± 3 mGy) was performed at 120 kV with automatic exposure control, and reconstructed with FBP. The ULD examination (1.5 ± 0.4 mGy) was performed at 120 kV and fixed tube current of 17 to 20 mAs/slice to achieve ULD radiation dose, with the rest of the scan parameters same as SD examination. The ULD data were reconstructed with (a) FBP, (b) iDose, and (c) SafeCT. Lesions were detected on ULD FBP series and compared to SD FBP "reference-standard" series. True lesions, pseudolesions, and missed lesions were recorded. Four abdominal radiologists independently blindly performed subjective image quality. Objective image quality included image noise calculation and noise spectral density plots. Results All true lesions (n, 52: liver metastases, renal cysts, diverticulosis) in SD FBP images were detected in ULD images. Although there were no missed or pseudolesions on ULD iDose and ULD SafeCT images, appearance of small low-contrast hepatic lesions was suboptimal. The ULD FBP images were unacceptable across all patients for both lesion detection and image quality. In patients with a body mass index (BMI) of 25 kg/m2 or less, ULD iDose and ULD SafeCT images were acceptable for image quality that was close to SD FBP for both normal and abnormal abdominal and pelvic structures. With increasing BMI, the image quality of ULD images was deemed unacceptable due to photo starvation. Evaluation of kidney stones with ULD iDose/SafeCT images was found acceptable regardless of patient size. Image noise levels were significantly lower in ULD iDose and ULD SafeCT images compared to ULD FBP (P < 0.01). Conclusions Preliminary results show that ULD abdominal CT reconstructed with iterative reconstruction techniques is achievable in smaller patients (BMI ⩽ 25 kg/m2) but remains a challenge for overweight to obese patients. Lesion detection is similar in full-dose SD FBP and ULD iDose/SafeCT images, with suboptimal visibility of low-contrast lesions in ULD images.